Exploring Research Trends and Themes in Intelligent Transportation Systems in the Last 10 Years (2014 – 2023) - Hasrul, M. Reza; Rahman, Mohammad Junaedy; Helmy, Ahnaf Riyandirga Ariyansyah Putra; Cheng, Aw Yoke; Ahsan, Muhammad (International Journal of Environment, Engineering and Education, 2023)
Intelligent Transportation Systems (ITS) are actively working towards transforming transportation systems by implementing solutions that improve the quality and quantity of transportation and traffic data at both individual and collective levels. This research aims to comprehensively analyze the field of Intelligent Transportation Systems (ITS) through a thorough bibliometric analysis covering the period from 2014 to 2023. The goal is to gain an in-depth understanding of the evolution of ITS research. This research employs bibliometric analysis to uncover trends and patterns in studies related to "Intelligent Transportation Systems." The research data is sourced from the Scopus database, encompassing information from document titles, abstracts, and keywords. The time frame considered for this study spans from 2014 to 2023. Studies were identified using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) framework. From the 39,846 records identified from the Scopus database, 1,839 studies were included in the analysis. Subsequently, the results are analyzed using the VOS viewer software. The analysis highlights a significant shift in research focus, with core themes like "intelligent transportation sys," "vehicle," "algorithm," and "system" remaining central. Cybersecurity and associated risks have gained prominence due to increased connectivity in ITS. The study identifies promising research directions, including experimental technology validation, real-time traffic management solutions, and IoT and smart city concept integration. This research provides a comprehensive and novel overview of the ITS field's evolution and trends, offering actionable insights for advancing intelligent transportation systems.